Experimental Study on the Development Characteristics and Controlling Factors of Microscopic Organic Matter Pore and Fracture System in Shale - Zhang, Qin; Liu, Zaiyang; Liu, Chang; Zhu, Xiaomin; Steel, Ronald J.; Tian, Hanyun; Wang, Kai; Song, Zeping (Frontiers in Earth Science, 2021)
Research on microscopic pore and fracture system of shale gas reservoir is a hot spot in the field of unconventional oil and gas exploration. Micro- and nano-scale pores, especially organic matter pores, play a vital role in the enrichment of shale gas. Research on the types, distribution, evolution rules and controlling factors of organic pore-fracture system in shale reservoirs provides a scientific guidance for the prediction of shale sweet spots. In this paper, taking the shales from the Napo Formation, Oriente Basin, the Shahejie Formation, Zhanhua Sag, Bohai Bay Basin, and the Longmaxi and Wufeng Formations, Sichuan Basin as examples, the development characteristics of shale organic matter pore-fracture system were systematically studied using thin section, argon ion profiling scanning electron microscopy, X-ray diffraction, N2 adsorption and desorption, organic matter geochemistry experiments and image processing technology. The organic matter pore types of shale were divided into kerogen-hosted pores, organic matter microfractures (intra-organic matter and organic matter edge microfractures), and asphalt pores (intra-asphalt pores). The increase in the degree of thermal evolution is the dynamic cause of the gradual rounding of organic pores, and the directional properties of the pores is strengthened as well. Internal factors (abundance of organic matter, kerogen type and maturity) and external factors (diagenesis and mineral composition) control the development of shale organic matter pores. Maturity and TOC content are positively correlated with the development of organic matter pores. In addition, Inorganic minerals such as clay minerals and pyrite can promote the enrichment of organic matter pores, while brittle minerals can cause a decrease in the face ratio of organic matter pores. Diagenetic compaction can cause the organic matter pores to deform or eventually disappear.